Welcome home Jellybean - Shyer, Marlene Fanta ([S.l.] : Collins Educational, 1978)
Neil's life turns upside down when his parents take his retarded sister out of an institution and bring her home to stay.
Keywords: Mentally handicapped -- Fiction; People with mental disabilities -- Fiction; Siblings -- Fiction